Stabilization Activities by Underwriters after Initial Public Offerings - Aggarwal, Reena (Journal of Finance, 2000)
Prior research has assumed that underwriters post a stabilizing bid in the aftermarket. We find instead that aftermarket activities are less transparent and include stimulating demand through short covering and restricting supply by penalizing the flipping of shares. In more than half of IPOs, a short position of an average 10.75 percent of shares offered is covered in 22 transactions over 16.6 days in the aftermarket, resulting in a loss of 3.61 percent of underwriting fees. Underwriters manage price support activities by using a combination of aftermarket short covering, penalty bids, and the selective use of the overallotment option.